Watershed simulation using GIS integrated physically based model - DIVYA GOPINATH; Kripa I. V; Pooja P; Shalini M. CHandran; Er. K. K Sathian (Guide) (Tavanur 2009 Department of Land and Water Resources and Conservation Engineering)
Watershed simulation using GIS integrated physically based model
Watershed simulation using GIS integrated physically based model